2019
DOI: 10.1016/j.abrep.2018.100144
|View full text |Cite
|
Sign up to set email alerts
|

Need fulfilment and internet gaming disorder: A preliminary integrative model

Abstract: Background The need for a better understanding of the risk factors underpinning disordered gaming has been consistently emphasized. Although, gaming may offer a simple and straightforward means of alleviating distress, relying on gaming to address one's unmet psychological needs could invite problematic usage. Self-determination theory highlights the significance of three universally inherent psychological needs for relatedness, competency, and autonomy. A motivation to engage in gaming may be to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 45 publications
(78 reference statements)
1
35
0
Order By: Relevance
“…The findings of the previous study, as outlined above, contribute to the hypothesis that individual CSE traits may mediate excessive gaming behavior (Beard & Wickham, 2016;Gervasi et al, 2017;Scerri, Anderson, Stavropoulos, & Hu, 2018). In addition, there is evidence of the role of maternal and paternal rejection (PARTheory) in predicting impaired self-esteem and/or self-efficacy (Chong, Yeo, & Mislan, 2014;Dural & Yalcin, 2014).…”
Section: Introductionmentioning
confidence: 54%
“…The findings of the previous study, as outlined above, contribute to the hypothesis that individual CSE traits may mediate excessive gaming behavior (Beard & Wickham, 2016;Gervasi et al, 2017;Scerri, Anderson, Stavropoulos, & Hu, 2018). In addition, there is evidence of the role of maternal and paternal rejection (PARTheory) in predicting impaired self-esteem and/or self-efficacy (Chong, Yeo, & Mislan, 2014;Dural & Yalcin, 2014).…”
Section: Introductionmentioning
confidence: 54%
“…As previously discussed, psychological compensation and compensatory behaviors can extend beyond avatar customization and body image, as gamers can attempt to compensate in areas other than appearance (Stavropoulos et al, 2018d;Stavropoulos et al, 2019). Individuals who may feel lonely and lacking social connections in the real world can find solace in online socialization, in which they might experience higher acceptance by a guild; that is, a group of gamers supporting each other consistently throughout the game (Stavropoulos et al, 2017;Scerri, Anderson, Stavropoulos, & Hu, 2018). Within guilds, gamers may feel a greater sense of purpose and belongingness, and therefore, compensate for their potential lack of socialization in the real world by becoming meaningfully and socially involved in the virtual world (Goodman, Doorley & Kashdan, 2018).…”
Section: Compensation and Igdmentioning
confidence: 99%
“…There is a wide range of game genres, these can include racing, shooting, puzzle, fighting, simulation, and role-playing games, available both in single player and/or multiplayer formats ( Anderson et al, 2017 ; Hu, Stavropoulos, Anderson, Scerri, & Collard, 2018 ; Scerri, Anderson, Stavropoulos, & Hu, 2018 ). Recent studies have shown that IGD susceptibility appears to vary across these game genres, with MMO games consistently corresponding with a higher risk due to its unique structural characteristics ( Kuss & Griffiths, 2012 ; Stavropoulos, Kuss, et al, 2017 ; Stavropoulos, Wilson, Kuss, Griffiths, & Gentile, 2017 ; Stetina et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%